Pulmonary Isolation of Multidrug resistant "Mycobacterium simulans" and Mycobacterium tuberculosis from a patient in the Horn of Africa. Issue 1 (December 2018) - Bouzid, Fériel; Osman, Djaltou; Baptiste, Emeline; Delerce, Jeremy; Hassan, Mohamed; Arreh, Warsama; Levasseur, Anthony; Garnotel, Eric; Drancourt, Michel
Abstract In low-income countries of the Horn of Africa, pulmonary infections are usually considered as tuberculosis, which diagnosis relies on clinical data and positive microscopic observation. This strategy allows non-tuberculous mycobacteria to escape detection, facilitating their emergence in populations. A non-tuberculous mycobacterium strain FB-527 was unexpectedly cultured from the sputum of a Djiboutian patient otherwise diagnosed with multi-drug resistant (MDR) tuberculosis. The sequencing of therpoB and 16S rRNA genes showed that the isolate was identical to strain FI-09026 previously named "Mycobacterium simulans " and reported only once from a Somali patient. Strain FB-527 mimickedMycobacterium tuberculosis colonies and enzymatic profile using API ZYM strip and wasin vitro resistant to rifampicin and isoniazid. Isolation of two MDR mycobacteria complicated the diagnosis and therapeutic management of the patient. We here report on the complete description of strain FB-527 and strain FI-09026 including genome sequencing, finalizing the description of the proposed new species "Mycobacterium simulans ".